Optimization of IPS Learning with the Concept of Cooperation in the Neighborhood for Students of Class 2 MI Al-Whataniyah 1 Jakarta - Rosfiani, Okta; Bakry, M. Haikal; Aripin, Bustamil; Wulan, Dewi; Azzahra, Fatimah (MASALIQ, 2025)
This research aims to analyze the effectiveness of the concept teaching model in improving social studies learning outcomes on the material of cooperation in the neighborhood environment. The researchers used the Classroom Action Research method with two cycles. The study was conducted at MI Al Wathaniyah 1 North Jakarta with 34 class 2 students as subjects. Data collection was carried out through systematic observation, in-depth interviews, documentation, and learning outcome tests. Data analysis used qualitative and quantitative descriptive techniques. The research results showed a significant increase in student learning outcomes after the implementation of the concept teaching model with classical completeness reaching 85% in cycle II. The average student learning outcomes reached 90%. In addition, the teacher's teaching activities also showed an achievement of 100%. It means that the activity shows the teacher's ability to master the class and apply the concept teaching model well. Student presentations in observing and answering worksheets or written tests also reached 85%. Therefore, this study contributes to the development of a more effective social studies learning methodology at the elementary education level.